On the impact of caching and a model for storage-capacity measurements for energy conservation in asymmetrical wireless devices - Mavromoustakis, Constandinos X. (My University, 2008)
Traffic and channel-data rate combined with the stream oriented methodology can provide a scheme for offering optimized and guaranteed QoS. In this work a stream oriented modeled scheme is proposed based on each nodepsilas self-scheduling energy management. This scheme is taking into account the overall packet loss in order to form the optimal effective -for the end-to-end connection- throughput response. The scheme also -quantitatively- takes into account the asymmetrical nature of wireless links and the caching activity that is used for data revocation in the ad-hoc based connectivity scenario. Through the designed middleware and the architectural layering and through experimental simulation, the proposed energy-aware management scheme is thoroughly evaluated in order to meet the parameterspsila values where the optimal throughput response for each device/user is achieved.